(untitled) (Academia Journal of Medicine, 2021)
Background: WHO estimates that with continued escalation of HIV transmission, nearly 9 million HIV-infected people will reside in South-East Asia by the turn of the century. In India, two new infections occur every minute. National Aids Control Organization (NACO) estimates that by year 2025 the majority of new HIV infections in the world will occur in Asia and India will probably have the largest number of infected persons of any single country. The objectives is to study the baseline values of CD+ count in newly diagnosed to be infected with Human Immunodeficiency Virus (HIV). SubjectsandMethods: The present cross sectional study was conducted at Shri B M Patil Medical College and Hospital, Bijapur form March 2017 to April 2018. A total of 100 newly Diagnosed HIV Patients of all Age Group either asymptomatic or presenting with one or other opportunity infections are included in the study. Results: 39% of them were in the age group of 35-45 years. Cough fever and weight loss were the most common clinical presentation on admission. The most common opportunistic infection at presentation was Pulmonary Tuberculosis (74%). followed by Candidiasis (62%). Among the population studied, majority were in the 35-45 yr. age group (39) out of which 25 individuals had a CD 4 count of< 200 cells/3. In the patients with CD 4 Count less than 200 cell extra pulmonary tuberculosis was most common. Candidiasis was also seen in the patients with CD4 count less than 200 cell/l. Conclusion: The most common route of transmission was the sexual route, predominantly heterosexual route.. The patients being diagnosed with HIV infection present with one or more of the opportunistic infections and frequently have a CD 4+ count < 200 cells/l. This calls for increasing awareness about HIV in the general population so as to identify the disease at the earliest.